2013
DOI: 10.1177/0023677213501658
|View full text |Cite
|
Sign up to set email alerts
|

Considerations to maximize fat mass gain in a mouse model of diet-induced weight gain

Abstract: Mouse experimental models of diet-induced weight gain are commonly used as analogs to human obesity; however, a wide variety of feeding methods have been used and the most effective way to maximize weight gain is not known. Maximizing weight gain may allow for a reduction in the number of animals required for a given experiment. The purpose of this study was how to cause the greatest amount of weight gain in CD-1 mice by modifying the composition and source of their diet. To accomplish this goal, we completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Due to the association between adipose tissue inflammation, insulin resistance and steatosis, diets high in saturated fat are often used to model obesity, glucose intolerance and NAFLD in mice (56) . Due to the association between adipose tissue inflammation, insulin resistance and steatosis, diets high in saturated fat are often used to model obesity, glucose intolerance and NAFLD in mice (56) .…”
Section: Murine Models Best For Diet-induced Non-alcoholic Fatty Livementioning
confidence: 99%
See 3 more Smart Citations
“…Due to the association between adipose tissue inflammation, insulin resistance and steatosis, diets high in saturated fat are often used to model obesity, glucose intolerance and NAFLD in mice (56) . Due to the association between adipose tissue inflammation, insulin resistance and steatosis, diets high in saturated fat are often used to model obesity, glucose intolerance and NAFLD in mice (56) .…”
Section: Murine Models Best For Diet-induced Non-alcoholic Fatty Livementioning
confidence: 99%
“…Due to the association between adipose tissue inflammation, insulin resistance and steatosis, diets high in saturated fat are often used to model obesity, glucose intolerance and NAFLD in mice (56) . Comparison of diets ranging in fat from 30 to 60 % demonstrated that a diet containing >45 % of energy from fat results in the greatest weight gain after 18 weeks of treatment in CD-1 mice (56) . Comparison of diets ranging in fat from 30 to 60 % demonstrated that a diet containing >45 % of energy from fat results in the greatest weight gain after 18 weeks of treatment in CD-1 mice (56) .…”
Section: Murine Models Best For Diet-induced Non-alcoholic Fatty Livementioning
confidence: 99%
See 2 more Smart Citations
“…In this issue several articles are published with relevance to diets and animal experimentation. [1][2][3][4][5][6] One needs to realize that feeding laboratory animals has become important and questions arise on the content of chow pellets, the consistency or variations in food pellet formulae according to specific diets, or research objectives. It has long been known that diets may affect health and longevity, or influence a variety of diseases, 7,8 including many types of cancer, cardiovascular diseases, obesity, behavioral or age-related changes and cognition.…”
Section: On the Importance Of Food Beat M Riederermentioning
confidence: 99%